PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi Pada Hotel Dyan Graha Pekanbaru) - Rimma Roslika Situmorang; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at Hotel Dyan Graha Pekanbaru, as for the purpose of this study was to determine the effect of the marketing mix and service quality to customer loyalty (study at Hotel Dyan Graha Pekanbaru). Marketing mix and service quality as the independent variable (X1X2 while the customer loyalty as the dependent variable (Y).The problem in this research is the sale of room service of Hotel Dyan Graha Pekanbaru fluctuated and tended to decline each year, does not even reach the sales target. Seen from the presentation realization penjulan services of a hotel room in the last 4 years. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS.From the test results which shows that the marketing mix and service quality have a positive and significant impact on customer loyalty (study at Hotel Dyan Graha Pekanbaru).Key words: marketing mix, Service Quality and Customer loyalty